2017
DOI: 10.1038/cddis.2016.429
|View full text |Cite
|
Sign up to set email alerts
|

RNY (YRNA)-derived small RNAs regulate cell death and inflammation in monocytes/macrophages

Abstract: The recent discovery of new classes of small RNAs has opened unknown territories to explore new regulations of physiopathological events. We have recently demonstrated that RNY (or Y RNA)-derived small RNAs (referred to as s-RNYs) are an independent class of clinical biomarkers to detect coronary artery lesions and are associated with atherosclerosis burden. Here, we have studied the role of s-RNYs in human and mouse monocytes/macrophages and have shown that in lipid-laden monocytes/macrophages s-RNY expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…Since the total RNA sequencing have limited capability in examining all short RNA fragments, smRNA sequencing was also performed by a ligation-based sequencing method [36], whose optimal templates are 5ʹ phosphorylated RNAs, such as miRNA and those smRNA derived from tRNA (tRFs) and Y_RNA (RNY) but act like miRNA [37,38]. Carious smRNA species were observed that mapped to miRNA, tRFs, RNY, piRNA as well and lincRNA with length range from 18 to 40 nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…Since the total RNA sequencing have limited capability in examining all short RNA fragments, smRNA sequencing was also performed by a ligation-based sequencing method [36], whose optimal templates are 5ʹ phosphorylated RNAs, such as miRNA and those smRNA derived from tRNA (tRFs) and Y_RNA (RNY) but act like miRNA [37,38]. Carious smRNA species were observed that mapped to miRNA, tRFs, RNY, piRNA as well and lincRNA with length range from 18 to 40 nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, different types of Y-RNA (mY1 and mY3 in mice and hY1, hY3, hY4, and hY5 in humans) have been detected in EV from a multitude of different cell types and in different body fluids [ 30 32 , 34 , 35 , 77 81 ]. The extracellular presence of Y4- and Y5-RNA and fragments thereof has mostly been associated to cancer [ 32 , 81 , 84 , 102 ] and coronary artery disease [ 78 , 103 ]. Immune-related functions of Y-RNAs include their capacity to trigger TLR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions with this pathway were not studied for YRNA to date and would probably also provide the explanations for aberrant YRNA expression. It may also be speculated that YRNAs are secreted by BCA cells to act as mediator of immunoescape: extracellular YRNAs fragments activate TLR7 to promote apoptosis in macrophages and monocytes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…YRNAs are overexpressed in various cancer cells [ 11 ], and RNY1 and RNY3 inhibition was shown to decrease cell proliferation [ 11 , 12 ]. YRNA-derived fragments are involved in caspase-3-dependent cell death and NF-κB-dependent inflammation and may have an inflammatory role [ 13 ]. It was also shown that RNY5 fragments in extracellular vesicles trigger cell death, and thereby may help cancer cells to optimize the microenvironment for proliferation and invasion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%